ChemInform Abstract: Transition‐Metal‐Free, Potassium tert‐Butoxide/Dimethyl Sulfoxide Mediated Amination Between Tertiary Amines and Aryl Halides. Issue 23 (June 2015) - Huang, Pei; He, Bang‐Yue; Wang, Hui‐Min; Lu, Jian‐Mei
Abstract The C—N coupling of aromatic and tertiary amines with aryl halides is achieved.